Implementation of the state policy for innovative development of the heat supply sector - Yu. O. Bakrunov; V. V. Glazkova (Vestnik MGSU)
Introduction. The state policy in the sphere of heat supply, aimed at improving the efficiency and reliability of this sphere, as well as achieving its energy security property, is implemented through the functioning of unified heat supply organizations (UHSO), acting as the centre of responsibility, modernization and technological development of heat supply in the assigned territory. One of the priority directions of modernization of heat supply is its innovative development, therefore the purpose of the study is to consider the directions of state policy implementation in the issues of innovative development of the heat supply sector, in particular, the study of issues of innovative development of UHSO. The process of innovation implementation in the study is represented by three main stages — preparatory, implementation and final. Consideration of the content characteristics of the preparatory stage made it possible to identify the methods of introducing innovations into unified heat supply organizations and the tools corresponding to the methods. In the course of studying the features of the implementation stage of innovation, the sequence of the implementation stage of innovation in relation to the unified heat supply organizations, taking into account their specifics, is determined. The description of the final stage made it possible to detail the processes of monitoring and control over the implementation of innovations in UHSO.Materials and methods. The normative basis of the study was the legislative acts of the Russian Federation regulating the heat supply activities and determining the directions of state policy in the sphere under consideration. The theoretical basis of the research is the works of Russian and foreign authors on the issues of development, modernization, technical re-equipment of the heat supply sector and its innovative development. The methods of empirical and theoretical levels are the methodological basis.Results. The result of the research is the developed methodological approach to the introduction of innovations into unified heat supply organizations authorized to implement the state policy in the sphere of heat supply, including the identification of the features of the preparatory, implementation and final stages of innovation in the organization.Conclusions. The strategic prospects of the heat supply sphere development fixed by the legislation provide for the implementation of programmes of innovative development of heat supply, which should be supported by the state, and the implementation should be carried out by unified heat supplying organizations responsible for the development of the heat supply system in the territory assigned to them, which makes it expedient to consider in detail the issues of innovative development of the heat supply subject implementing the state policy in the heat supply sphere.